Pengaruh Pendidikan Kesehatan dengan Booklet Diet Hemodialisa (BookET Lisa) Terhadap Tingkat Pengetahuan dan Sikap Pasien Hemodialisa di RSUD dr. RM. Pratomo Bagansiapiapi - Ezdha, Awaliyah Ulfah Ayudytha; Hamid, Abdurrahman; Fitri, Dwi Elka; Anggreini, Silvia Nora; Julianti, Elli Elfiza (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: One of the therapies for patients with chronic kidney is hemodialysis. Hemodialysis aims to eliminate the remnants of metabolic products or protein and as a correction of fluid and electrolyte balance disorders. In addition, this dialysis procedure can also cause complications, including affecting nutritional status. Some patients have difficulty managing nutritional intake but they do not get an understanding of how strategies can help them in managing nutritional diets. The strategy that needs to be done is providing health education using booklets on nutritional diets for hemodialysis patients. Objective: The purpose of this study is to determine the effect of health education with a media booklet on a nutritional diet on the knowledge and attitudes of hemodialysis patients in RSUD DR RM. Pratomo Bagansiapiapi. The number of respondents in this study was 27 respondents. Method: This research is a quantitative study using pre-experimental design research in the form of a pretest-posttest design with one group design. Based on the results of the T-test Dependent. The number of respondents in this study was 27 respondents. Results: It was obtained that the p-value (0,000) of knowledge and attitudes was smaller than 0.05. Conclusion: the conclusion of this study is there is a significant difference in knowledge and attitudes before and after being given health education about media booklet the nutritional diet of hemodialysis patients.